Stress Transiently Affects Pavlovian-to-Instrumental Transfer - Morgado, Pedro; Silva, Miguel; Sousa, Nuno; Cerqueira, João J. (Frontiers in Neuroscience, 2012)
Stress bias decision-making processes by favoring the shift to habits as a result of changes in corticostriatal circuits. Given that these same circuits are implicated in action control and outcome encoding implicated in adaptive responses we herein assessed the impact of chronic stress in a pavlovian-to-instrumental transfer (PIT) paradigm. Data reveals that rats submitted to a chronic unpredictable stress model did not display deficits in pavlovian conditioning nor on the learning of instrumental task, but were impaired in PIT; importantly, after a stress-free period the PIT deficits were no longer observed. These results are relevant to understand how stress bias multiple incentive processes that contribute to instrumental performance.